Synthesis and Characterization of Some Iridium(III) Complexes of Thiosemicarbazones of 4-Aminoantipyrine - Chakraborti, Indranil (Asian Journal of Chemistry, 2012)
In the present work, the synthesis of iridium(III) chloride complexes of ten thiosemicarbazones derived from 4-aminoantipyrine and various aromatic aldehydes has been reported. All the complexes have been characterized by elemental analyses, magnetic moments, infrared and electronic spectral studies. These complexes were found to have the composition [Ir(L)Cl3] and have octahedral stereochemistry (L = various thiosemicarbazones).